Grafen içeren poliimid köpüklerin sentezi ve karakterizasyonu - Kılıç, Volkan (My University, 2019)
Poliimid köpükler, yüksek termal ve mekanik özellikleri nedeniyle, havacılık ve uzay endüstrisi gibi ileri endüstriler için uygun malzemelerdir. Bu çalışmada izosiyanat bazlı poliimid köpükler tek basamaklı sentez yöntemi ve yarı-prepolimer yaklaşımı ile sentezlenmiştir. Çalışmada benzofenon tetrakarboksilik asit anhidrit (BTDA) ve piromellitik anhidrit (PMDA) olmak üzere iki farklı anhidrit ile %0, %0,25, %0,50, %0,75 ve %1 oranlarda grafen oksit (GO) içeren köpükler sentezlenmiş, konik kalorimetre ve limit oksijen indeksi analizleri ile termal özellikleri incelenmiştir. Bunun yanında basma testi ile mekanik özellikler, taramalı elektron mikroskobu ile de morfolojik özellikleri incelenmiştir. GO içeren sistemlerin dışında BTDA ile farklı oranlarda su ve surfaktan içeren iki ayrı sistem daha sentezlenmiş, bu köpükler de basma testi ile mekanik ve SEM ile morfolojik açıdan incelenmiştir.

Polyimide foams are highly useful materials for advanced industries such as aerospace and aviation because of their great thermal and mechanical properties. Isocyanate based graphene oxide containing polyimide foams were synthesised by the one-pot method and the semi-prepolymer approach in this study. There are two different anhydride monomer that was used as 3,3’ ,4,4’ benzophenone tetracarboxylic acid dianhydrate (BTDA), pyromellitic dianhydrate (PMDA) with different graphene oxide ratios such as 0 wt.%, 0,25 wt.%, 0,50 wt.%, 0,75 wt.%, 1 wt.% respectively. Thermal properties of synthesised foams were investigated via Cone Calorimeter and Limiting Oxygen Index analysis. Mechanical properties of foams were studied via compression analysis, and morphological properties were observed via Scanning Electron Microscope (SEM). On the other hand, two different foam system were synthesized with BTDA that includes water and surfactant with different ratios and not including graphene oxide. These foams mechanical properties also researched via compression test and morphological properties observed via SEM analysis.
Keywords: foam; grafen polyimide; graphene; köpük; Metallurgy; Metalurji; poliimid